Current status and biotechnological development of Etlingera elatior, a promising horticultural and medicinal plant - Yunus, Muhamad Fahmi; Meenakshi Sundram, Tamil Chelvan; Zainuddin, Zarina; Ismail, Nor Asiah; Mohd Rosli, Norsalsabila; Mohamad Hamdan, Mohd Syafik (Taylor and Francis Ltd., 2022)
Etlingera elatior (Jack) which belongs to Zingiberaceae family is one of the most commonly known species of Etlingera. E. elatior has been traditionally used for many different purposes and have a long history of traditional uses in Southeast Asia. Every part of this plant has significant economic value. It can be used as material source in preparing traditional medicines, while the young inflorescences are used as herbs and food ingredients in Southeast Asia. Recently, E. elatior is gaining attention as ornamental plant due to its colourful and attractive inflorescences. On top of that, modern-day horticulture industry is based on creating variation, selection, evaluation, and multiplication of desired genotypes. There is always a demand for the horticulture industry to maintain its competitiveness by producing new cultivars with appeal for cut flower. Furthermore, new cultivars of promising quality can be used for commercial cultivation and as new source of genes for breeding programme. Due to its popularity, E. elatior is also being researched for its pharmacological activities, medicinal properties and potential applications in nanotechnology. This review provides research on E. elatior, including, nutritional composition, phytochemical compounds, bioactivities, plant tissue culture, in vitro mutagenesis, molecular marker, and bioinformatics of this precious horticultural plant.